Islam and Good Governance - Khan, M. A. Muqtedar. author. aut Link
XXI, 278 p. 82 illus.
Keywords: This book advances an Islamic political philosophy based on the concept of Ihsan, which means to do beautiful things. The author moves beyond the dominant model of Islamic governance advanced by modern day Islamists. The political philosophy of Ihsan privileges process over structure, deeds over identity, love over law and mercy and forgiveness over retribution. The work invites Muslims to move away from thinking about the form of Islamic government and to strive to create a self-critical society that defends national virtue and generates institutions and practices that provide good governance. M. A. Muqtedar Khan is Professor at the University of Delaware, USA. He is a scholar of Islamic Thought, Governance and International Relations.